2017
DOI: 10.1088/1361-6560/aa86e3
|View full text |Cite
|
Sign up to set email alerts
|

An electromechanical, patient positioning system for head and neck radiotherapy

Abstract: In cancer treatment with radiation, accurate patient setup is critical for proper dose delivery. Improper arrangement can lead to disease recurrence, permanent organ damage, or lack of disease control. While current immobilization equipment often helps for patient positioning, manual adjustment is required, involving iterative, time-consuming steps. Here, we present an electromechanical robotic system for improving patient setup in radiotherapy, specifically targeting head and neck cancer. This positioning sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The mechanical positioning accuracy of this system was less than that of other similar robotic applications, such as those presented by Liu 12 or Ostyn 11 . For example, our previously introduced system had a positioning error of 0.4 ± 0.3 mm error, compared to the 0.7 ± 0.3 mm of the system in this work.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…The mechanical positioning accuracy of this system was less than that of other similar robotic applications, such as those presented by Liu 12 or Ostyn 11 . For example, our previously introduced system had a positioning error of 0.4 ± 0.3 mm error, compared to the 0.7 ± 0.3 mm of the system in this work.…”
Section: Resultsmentioning
confidence: 75%
“…All materials used in the positioning robotic system were carefully selected to minimize the effects of scatter and attenuation during radiotherapy. Based on the similar method from our prior work 11 , we conducted a more rigorous method for prospectively assessing radio-compatibility for any arbitrary material. All components within 40 cm horizontally of the positioning system’s isocenter were constructed by fully using low-Z materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the systems excluding the 6DoF couch, Dhabaan et al reported that pitch and roll angles can be corrected by mounting the customized device on the top of the treatment couch in the cranial position . Belcher et al and Ostyn et al developed an electromechanical robotic system that can provide precise 6DoF motion trajectories . These systems can correct the rotational position of the patient by themselves; therefore, they might be able to correct the twist with the couch, which has the ability to achieve rotational correction.…”
Section: Discussionmentioning
confidence: 99%